Energy, exergy and economic assessments of a novel integrated biomass based multigeneration energy system with hydrogen production and LNG regasification cycle. (15th April 2017) - Taheri, M.H.; Mosaffa, A.H.; Farshi, L. Garousi
Abstract: In this work, a novel integrated biomass based multigeneration energy system is presented and investigated for power, cooling and hydrogen production. The proposed system consists of a combination of biomass integrated gasifier-gas turbine cycle, a Rankine cycle, a cascade organic Rankine cycle, an absorption refrigeration system and a PEM to produce hydrogen. This system uses cold energy of LNG as a thermal sink. Comprehensive thermodynamic and economic analyses as well as an optimization are performed. The effects of operating parameters on thermodynamic performance and total cost rate are investigated for overall system and subsystems. The results show that the fuel mass flow rate is the dominant factor affecting the variation of energy efficiency and total cost rate. An increase in fuel mass flow rate from 4 kg s −1 to 10 kg s −1 leads to a decrease of 8.5% and an increase of 122.8% overall energy efficiency and total cost rate, respectively. Also, the largest increase in exergy efficiency occurs when gas turbine inlet temperature increases. The results of optimization showed that the highest net power output, mass flow rate of natural gas delivered to city and the flue gas temperature discharged to the environment are obtained for the exergy efficiency optimal design. Highlights: A novel multigeneration system is investigated and optimized thermodynamically and economically. This system is proposed for power, cooling and hydrogen production. Proposed system uses LNG cold energy thermal sink that can generate power after vaporization. The effects of operating parameters on energy and exergy efficiencies and total cost rate are investigated. An optimization is applied based on the energy, exergy and economic viewpoints.